First record of the endemic Neotropical genus Hyphydrophilus (Chilopoda: Geophilomorpha, Geophilidae) from Argentina, with description of H. minellii sp. nov., a new centipede with small tentorial process, inhabiting the Yungas - Pereira, Luis Alberto (2016)
A new miniature species of the endemic Neotropical genus Hyphydrophilus (Chilopoda: Geophilomorpha, Geophilidae) is described and illustrated, after the holotype female and paratype female, from the Yungas rainforest of Salta province, northwestern Argentina. H. minellii sp. nov. is compared in detail with the other two species currently assigned to the taxon, i.e. H. adisi Pereira, Minelli & Barbieri, 1994 and H. projectus Pereira, Foddai & Minelli, 2000, both from Brazil, from which it differs by the presence of a small slightly sclerotized and inwards directed process of internal limbs of tentorium. Other unique traits of the new taxon are the relatively high number of leg-bearing segments (59), antennal articles I–IV with numerous large setae on the latero-external side, apical medial edge of forcipular trochanteroprefemur with a well-developed slightly pigmented tooth, dorsal and ventral medial edges of the forcipular tarsungulum slightly serrate, sternal pore-fields present on anterior region of the trunk only. This is the first report of the genus Hyphydrophilus from Argentina and the Yungas forests; previously it was only known to occur in Central Brazilian Amazonia, thus the present record represents a remarkable extension of the known range of this taxon.